Farmers' Perception Towards Agroforestry Practices in Siburan - Jacklin, Mathew; MUHAMMAD HIBATULLAH, JAMALI; VANISHRI KALY, SITTHAN; Romia Rona, Tagang; Mohamad Hilmi, Ibrahim (UNIMAS Publisher, 2024)
Climate change increasingly affects agricultural output and productivity, prompting a search for resilient and sustainable land use practices. Among these, agroforestry has gained recognition as a crucial strategy, offering mitigation against climate change and providing environmental, economic, and social benefits. Agroforestry is a practice that integrates trees and crops for sustainable land management to mitigate climate change and generate income. Although there are successful pilot projects for wet rice cultivation in Kampung Skuduk and Kampung Chupak, agroforestry activities in the paddy fields have yet to be documented. Therefore, it is crucial to introduce agroforestry practices to farmers in order to diversify their income sources and aid in their adaptation to climate change. Thus, this study aimed to determine farmers’ perception towards agroforestry, as it will influence farmers’ attitudes and the likelihood of them adopting agroforestry practices to adopt agroforestry practice. Data was gathered via structured questionnaire interviews, employing a five-point Likert scale to evaluate respondents’ views on agroforestry. The data were analysed using SPSS and the trend of the composite score was used to interpret the five-point Likert scale data. The results show that the respondents have a positive attitude toward agroforestry practices. They also expected awareness-raising activities and workshops on agroforestry, indicating that they are willing to learn more about these practices. Eighty percent of respondents who do not practice agroforestry are interested in practicing agroforestry if there are no obstacles. This positive attitude indicates that farmers in the study area are ready and willing to practice agroforestry if there are no obstacles, because a positive attitude towards an agricultural innovation will increase the likelihood of adoption.